Villains or heroes? The raison d'être of viruses. Issue 2 (19th February 2020) - Watanabe, Tokiko; Kawaoka, Yoshihiro
Abstract: The relationship between humans and viruses has a long history. Since the first identification of viruses in the 19th century, we have considered them to be 'pathogens' and have studied their mechanisms of replication and pathogenicity to combat the diseases that they cause. However, the relationships between hosts and viruses are various and virus infections do not necessarily cause diseases in their hosts. Rather, recent studies have shown that viral infections sometimes have beneficial effects on the biological functions and/or evolution of hosts. Here, we provide some insight into the positive side of viruses. Abstract : Traditionally, viruses have been considered to be 'pathogens' that cause diseases in their hosts. In this review, we discuss recent studies that shed light on previously unrecognised beneficial roles of viruses in nature.